Nitrogen doped carbon quantum dots mediated silver phosphate/bismuth vanadate Z-scheme photocatalyst for enhanced antibiotic degradation - Zhang, Jin; Yan, Ming; Yuan, Xingzhong; Si, Mengying; Jiang, Longbo; Wu, Zhibin; Wang, Hou; Zeng, Guangming (Journal of colloid and interface science, 2018)
[Display omitted] A novel nitrogen doped carbon quantum dots (N-CQDs) mediated Ag3PO4/BiVO4 Z-scheme photocatalyst was synthesized through a solvothermal-precipitation method. The as-prepared photocatalysts were comprehensive characterized by X-ray diffraction, X-ray photo-electron spectroscopy, scanning electron microscopy, transmission electron micrograph, UV–vis diffuse reflection spectroscopy, vis photoluminescence and electron spin resonance analysis. The photocatalytic performances of as-prepared photocatalysts were used for degradation of tetracycline (TC) under visible-light illumination. Results exhibited the increased photocatalytic efficiency of BiVO4/N-CQDs/Ag3PO4-10 (Ag3PO4 with the mass ratio of BiVO4/N-CQDs/Ag3PO4 = 10%) to photodegrade TC is up to 88.9% in 30 min and 59.8% mineralization in 90 min. The degradation reaction coefficient (k) is about 6.00, 2.78 and 1.80 times higher than that of BiVO4, N-CQDs/BiVO4 and Ag3PO4/BiVO4, respectively. The excellent photocatalytic performance of the Z-scheme BiVO4/N-CQDs/Ag3PO4 was attributed to the construction of Z-scheme system, increased light harvesting capacity and improved molecular oxygen activation ability. Moreover, the photocatalytic activity of BiVO4/N-CQDs/Ag3PO4 remained 79.9% after five cycling runs, indicating the high stability and reusability of the as-prepared photocatalyst. Additionally, a possible photocatalytic mechanism of the novel Z-scheme BiVO4/N-CQDs/Ag3PO4 was proposed.